Perancangan Alat Penghitung Jumlah Pengunjung Konser Berbasis Mikrokontroler At89s51 - Eko Setia Budi (STMIK Budi Darma, 2018)
In the current era of globalization, information technology advanced so quickly. The computer is the equipment created to facilitate the work of man, while achieving good progress in the manufacture of hardware and software. For that I am as a writer tries final project for the manufacture of tools called